Relationship between job satisfaction, career commitment and organisational citizenship behaviour among primary school teachers in Kuala Lumpur, Malaysia - Subramaniam, Kantha Devi (2019)
In the growing demand of the teaching job and the teachers’ responsibility, the research on teachers’ organisational citizenship behavior might be beneficial to identify the factors that can cultivate this behavior and might be beneficial to identify areas of improvement. Therefore, the objective of the study is to examine the relationship between career commitment and job satisfaction as the two factors to study organisational citizenship behavior among primary school teachers. Even though the measures of job satisfaction, career commitment and organisational citizenship behavior been the research focus of numerous studies, there are limited studies conducted among primary school teachers, especially in Malaysia. Analysis of the relevant literature suggests that there are variety of factors that influnced workers’ organisational citizenship behavior across countries given the multitude of organisational commitment and job satisfaction.This study seeks to explore and understand the relationship between organisational citizenship behavior, career commitment and job satisfaction among primary school teachers from a Malaysian perspective. A quantitative survey was done using a self-administered questionnaire to gather data and information.Pilot test using the research instrument was administered prior to actual data gathering and it showed that the research instrument was safe to be administered to the selected sample. In this study, 370 primary school teachers were selected from primary schools in Kuala Lumpur using two-stages cluster sampling technique. Organisational citizenship behaviour was measured using instrument developed by Somech and Drach-Zahavy (2000). Meanwhile, career commitment was measured using Career Commitment Scale developed by Blau (1989) and Job Satisfaction Index developed by Schriesheim and Tsui (1980) was used to measure job satisfaction. Based on the findings, the result revealed that both career commitment and job satisfaction have positive significant influence on organisational citizenship behavior. Job satisfaction is found to be having greater influence towards the organisational citizenship behaviour of primary school teachers as compared to the career commitment. This study also provides insights and suggestions for future research on organisational citizenship behavior using other determinants.